Human culture and eco-systemic needs to inform innovayion within toilet design - Korculanin, Laura (2020)
ABSTRACT: Proposed paper is a part of the ongoing PhD research in design with focus on the research of existing environmental and social requirements for the sustainable innovation within urban sanita_on, focused on toilet design. Main questions of the research are aiming the Portuguese environment, where we are characterizing aspects of water and sanita_on through the five dimensions - culture, technology, government, economy, and environment. In this paper the main objective is to determine systemic characteristics of the socio-cultural dimension of water and sanitation, which will be later incorporated in writien final guidelines – directives raised from the research results which shall serve as operational knowledge for the ones involved in the implementation of the sustainable toilet innovation. The paper as well serves as theoretical orientation for the practical applications of the research.